Profitabilitas, Ukuran Perusahaan, Leverage, Eco-Control, dan Corporate Social Responsibility Disclosure - Sastrawan, I Komang Adi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p15, 2023)
Corporate Social Responsibility Disclosure is an information reporting carried out as a form of corporate social responsibility. The research aims to obtain empirical evidence of the influence of Profitability, Company Size, Leverage and Eco-control on CSR Disclosure. Research was conducted on SRI-KEHATI indexed companies on the IDX for the 2019-2020 period with a sample of 50 companies using the saturated sampling method. The analysis technique used is Multiple Linear Regression Analysis. The research results show that (1) profitability has a positive effect on CSR Disclosure, (2) company size has no effect on CSR Disclosure, (3) leverage has no effect on CSR Disclosure, (4) eco-control has a positive effect on CSR Disclosure. Keywords: Profitability; Company Size; Leverage; Eco-control; CSR Disclosure